Nahdlatul Ulama's Dedication to Promoting Religious Moderation: A Virtual Ethnographic Study of the NU Online Website - Liya Nikmah Jazhila; Imam Bonjol Juhari; Kun Wazis; Mohd Aashif bin Ismail (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The rise of hate speech, extremism, radicalism, and the deterioration of interfaith relations has become a prevalent issue within communities, especially in online media. Given the potential for this to cause division, it is crucial to approach the issue with moderation. This research focuses on exploring how the Nahdlatul Ulama Organization presents religious moderation on the NU Online website to promote values of goodness and demonstrate tolerance. The study used qualitative research methods and a virtual ethnography approach to analyze virtual texts and online media records. Data collection centered on selecting content related to religious moderation on NU Online media, and the analysis involved data reduction, display, and drawing conclusions. The research revealed that NU Online's moderate da'wah entails: Narrative of religious moderation as an option to gain Islamic insights, creating a virtual space to promote a calming religious spirit and present Islam as a universal religion ‘raḥmatan lil ālamīn’, and kindly promoting moderate Islam amidst the rapid influx of information in the media disruption era.